From Crisis to Innovation: Bridging the Digital Divide for Micro and Small Enterprises in Yogyakarta during the COVID-19 Pandemic - Helen Dian Fridayani; Li-Chun Chiang (Binus Business Review, 2025)
The research aimed to analyze the challenges faced by Micro and Small Enterprises (MSEs) in Yogyakarta, Indonesia, during the COVID-19 pandemic in adopting digital tools and platforms. The research explored the difficulties encountered by MSEs in Yogyakarta during the pandemic and their efforts to utilize digital solutions, employing a qualitative methodological approach and analyzing secondary data sources. Through in-depth interviews and Focus Group Discussions (FGDs) with 50 MSE owners and stakeholders, supplemented by document analysis of government policies, and existing studies, the research provided insights into the experiences, perceptions, and barriers to adopting digital innovations. Thematic coding of interview transcripts and data synthesis from secondary sources reveal recurring challenges such as financial constraints, limited Internet access, inadequate digital literacy, and insufficient technology infrastructure. Despite these obstacles, the research identifies a positive trend toward digitalization among MSEs, driven by the imperative to adapt to pandemic-induced disruptions and the growing recognition of the benefits of digital technologies. The analysis underscores the critical role of awareness-building, training, and infrastructure development in facilitating successful digital adoption. Additionally, the research highlights the necessity of government initiatives to support MSEs in overcoming the digital divide and emphasizes the importance of sector-specific strategies to address variations in digital adoption patterns. The research contributes to a nuanced understanding of digital adoption dynamics among MSEs in Yogyakarta. It suggests avenues for future research to explore the long-term impacts of digitalization on MSE sustainability and growth.